Panji Edu Eco Festival: Event Concept as a Sustainable Ecotourism Attraction Development in Panji Tourism Village, Buleleng Regency - I Nengah Wirata; I Putu Esa Widaharthana; Luh Putu Citrawati; I Gede Sumadi; IGA. Ratih Asmarani (Eduvest - Journal of Universal Studies, 2026)
This study aims to design the concept of the Panji Edu Eco Festival event as a thematic event that integrates agricultural practices with the development of sustainable ecotourism attractions in Panji Tourism Village, Buleleng Regency. This festival is expected to serve as an educational medium, promoting agrarian culture while supporting the achievement of sustainable development goals (SDGs). The study employs a descriptive qualitative method with a participatory action research approach. Data collection techniques include participant observation, in-depth interviews with subak farmers, community leaders, and tourism village managers, as well as documentation studies of existing subak conservation policies and practices. Data are analyzed thematically to formulate event elements that align with the values of sustainability and local wisdom. The novelty of this study lies in integrating the subak-based event model as a socio-ecological system with a community-based ecotourism approach, as well as in preparing a festival conceptual design that strengthens the narrative of agriculture as an educational and sustainable tourist attraction. The research results indicate that the Panji Subak Festivalhas the potential to reinforce local identity, increase community participation, and create opportunities for agro-ecotourism-based village economic diversification. The festival is also considered a potential intergenerational medium for transmitting subak values to the younger generation. A key recommendation is multi-stakeholder collaboration among farmers, tourism village managers, local governments, and academics to implement the festival sustainably as part of the village's annual agenda.